Influence of indications on perinatal outcomes after radio frequency ablation in complicated monochorionic pregnancies: a retrospective cohort study - Hongmei Wang; Qian Zhou; Xietong Wang; Jia Song; Pengzheng Chen; Yanyun Wang; Lei Li; Hongyan Li (BMC, 2021)
Abstract Background Radiofrequency ablation (RFA) is recommended to prevent potential neurological injury or intrauterine foetal death (IUFD) of the co-twin(s) in complicated monochorionic (MC) pregnancies. However, the impacts of various indications on the pregnancy outcome following RFA remain unclear. This study aimed to determine how the indications influence the perinatal outcomes in complicated MC pregnancies undergoing radiofrequency ablation. Methods This was a retrospective cohort study performed in a single centre. All consecutive MC pregnancies treated with RFA between July 2011 and July 2019 were included. The adverse perinatal outcomes and the survival rate were analysed based on various indications. The continuous variables with and without normal distribution were compared between the groups using Student's t-test and Mann-Whitney U test, respectively, and for categorical variables, Chi-square and Fisher's exact tests were used. P < 0.05 indicated a significant difference. Results We performed 272 RFA procedures in 268 complicated MC pregnancies, including 60 selective intrauterine growth restriction (sIUGR), 64 twin-twin transfusion syndrome (TTTS), 12 twin reversed arterial perfusion sequence (TRAPs), 66 foetal anomaly and 66 elective foetal reduction (EFR) cases. The overall survival rate of the co-twin was 201/272 (73.9%). The overall technical successful rate was determined at 201/263 (76.7%). The IUFD rate in the co-twin was 20/272 (7.4%). The TTTS group had recorded the lowest survival rate (37/64, 57. 8%), and the survival rate was significantly correlated with Quintero stages (P = 0.029). Moreover, the sIUGR III subgroup had a lower survival rate compared with sIUGR II (55.6%, versus 84.3%). The subgroup of foetal anomaly of gastroschisis or exomphalos had the highest IUFD rate (4/10, 40%), followed by sIUGR III (2/9, 22.2%) and dichorionic triamniotic (DCTA) subgroup (8/46, 17.9%). In EFR group, eight IUFD cases were all coming from the DCTA subgroup and received RFA before 17 weeks. Conclusions The perinatal outcome of RFA was correlated with the indications, with the lowest survival rate in TTTS IV and the highest IUFD incidence in abdominal wall defect followed by sIUGR III. Elective RFA after 17 weeks may prevent IUFD in DCTA pregnancies.